Arctic National Wildlife Refuge: Legislative Issues - Corn, M. Lynne; Gelb, Bernard A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2002)
This report discusses the ongoing debate about whether or not to open the Arctic National Wildlife Refuge (ANWR) for energy development. The report discusses arguments for and against such development and focuses especially on related pieces of legislation that directly affects the future of the ANWR.